Two part model analysis household out of pocket for traditional medicine consumption in Central Java - Haryka Fitra Perdana; Kurnia Sari (Berita Kedokteran Masyarakat (BKM), 2019)
Two part model analysis household out of pocket for traditional medicine consumption in Central JavaPurpose: Traditional medicine is primary health care that uses natural ingredients for treatment in accordance with norms in society. The proportion of traditional medicine utilization was 49% from all traditional health care. Based on Riskesdas 2013, Central Java was one of the provinces that had the highest proportion of traditional medicine utilization, which was 65.2%. This study aimed to determine traditional medicine expenditure in households in Indonesia based on socio-economy.Method: Method in this study was two part model assumption (probit) then compared with log linear value (non zero) ordinary least square (OLS) and also comparing two part model OLS with tobit model as output estimation.Results: The proportion of traditional medicine expenditure within total drugs expenditure was 15.33%. Variable of interest in this study was household region and economy status of household. From two part model (OLS) and tobit, it can be obtained that urban region and household that has expenditure above poverty line, could increase traditional medicine expenditure.Conclusion: This study showed that even though estimators from all situation did not significantly difference, but result from two part (OLS) models has higher coefficient value than tobit model.